(NoBU^ENIE INOSTRANCEW PORQDKU SLOW W RUSSKOM QZYKE (B/s - (NhAWRONINA(B, (NsERAFIMA aLEKSEEWNAs; (NkRYLOWA(B, (NoLXGA aLEKSEEWNAs ((NmOSKWA (B:s (NrUS(B. (NQZ(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 99-100s
Keywords: (NqZYKOZNANIEs